Peranan Home Industry Keripik Sayur Dalam Upaya Meningkatkan Kesejahteraan Keluarga - Syarifiyanti , Nurum; Suryati , Suryati; Isnaini , Mohd Aji (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Vegetable chips is one of the household industries in Pangkul Jawa Village which is still very traditional with its processing tools and strategies used and how to promote its products by entrusting products to souvenir centers and restaurants. The method used in this research is qualitative method. The types of data used are primary data and secondary data. Data collection techniques in this study were carried out through observation, interviews, and documentation. The purpose of making a thesis entitled "The Role of Vegetable Chips Home Industry in Efforts to Improve Family Welfare" is to be able to identify or know the potential role of the vegetable chips home industry in an effort to prosper the family. The research results obtained from this study are: 1. Regarding the strategy for home industry activities, namely by maintaining the quality of vegetable chip products with high quality and nutrition, as well as by improving technological systems to become more sophisticated. 2. Regarding the inhibiting factors in the home industry, namely the lack of manpower or human resources, the process of making vegetable chips production still uses traditional equipment. 3. Regarding the role of home industry activities, namely the existence of a chip-making business helps housewives earn additional income and it can be said that the existence of this chip business is very helpful for the economy and improves family welfare.